Are the Benefits of Export Support Durable? Evidence from Tunisia - Cadot, Olivier; Fernandes, Ana M.; Gourdon, Julien; Mattoo, Aaditya (World Bank, Washington, DC, 2013)
This paper evaluates the effects of the FAMEX export promotion program in Tunisia on the performance of beneficiary firms. While much of the literature assesses only the short-term impact of such programs, the paper considers also the longer-term impact. Propensity-score matching, difference-in-difference, and weighted least squares estimates suggest that beneficiaries initially see faster export growth and greater diversification across destination markets and products. However, three years after the intervention, the growth rates and the export levels of beneficiaries are not significantly different from those of non-beneficiary firms. Exports of beneficiaries do remain more diversified, but the diversification does not translate into lower volatility of exports. The authors also did not find evidence that the program produced spillover benefits for non-beneficiary firms. However, the results on the longer-term impact of export promotion must be interpreted cautiously because the later years of the sample period saw a collapse in world trade, which may not have affected all firms equally.